2004
DOI: 10.1097/01.mlr.0000124243.59446.5e
|View full text |Cite
|
Sign up to set email alerts
|

Recent Trends and Geographic Variation in the Safety Net

Abstract: Local financing capacity is a factor in variations across communities in the safety net. The economic downturn and pressures on state budgets could lead to future problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 15 publications
1
24
0
Order By: Relevance
“…In addition, policies oriented toward enhancing funding for the safety net and increasing the capacity of safety net providers are likely to be important to ensuring access among the urban uninsured. Researchers have reported a relatively stable trend in safety net capacity in the late 1990s through 2001 (Felland et al 2003), but the absolute level of capacity has been shown to vary widely across communities (Marquis et al 2004), and some research suggests that those disparities may be widening over time (Hoadley, Felland, and Staiti 2004). Increasing budgetary pressures at the federal level and in many states are likely to pose an increasing threat to safety net funding.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, policies oriented toward enhancing funding for the safety net and increasing the capacity of safety net providers are likely to be important to ensuring access among the urban uninsured. Researchers have reported a relatively stable trend in safety net capacity in the late 1990s through 2001 (Felland et al 2003), but the absolute level of capacity has been shown to vary widely across communities (Marquis et al 2004), and some research suggests that those disparities may be widening over time (Hoadley, Felland, and Staiti 2004). Increasing budgetary pressures at the federal level and in many states are likely to pose an increasing threat to safety net funding.…”
Section: Discussionmentioning
confidence: 99%
“…We measured safety-net capacity using the level of local government spending for health and hospitals in the metropolitan area. 11,17 Spending was scaled to the population with income Ͻ200% of the federal poverty line and was based on data obtained from the Census of Governments and the Annual Survey of State and Local Government Finances. We measured the primary care physician (PCP) supply in the local area as the sum of family practitioners, pediatricians, and general practitioners per thousand people in the county.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6] A review of this literature identified fourteen candidate programs for study, which in turn led us to additional programs. With advice from a national panel of safety-net experts, we selected model safety-net programs for uninsured people with incomes of up to 250 percent of the federal poverty level in four communitiesAsheville, North Carolina; Denver, Colorado; Flint, Michigan; and San Antonio, Texas.…”
Section: Study Data and Methodsmentioning
confidence: 99%